PENERAPAN PENDEKATAN PEMBELAJARAN COOPERATIVE LEARNING TIPE GROUP INVESTIGATION DALAM MENINGKATKAN HASIL BELAJAR IPA PESERTA DIDIK KELAS VIII-A SMP NEGERI 7 MATARAM - MADE SUKADANA (GANEC SWARA, 2018)
This research is a Classroom Action Research conducted at SMP Negeri 7 Mataram, in the second semester which aims to improve student learning outcomes in natural science learning through the use of Cooperative Learning approaches Type Group Investigation.      The subjects of this study were 37 students of class VIII-A of SMP Negeri 7 Mataram. This CAR is carried out in two cycles, where each cycle consists of 3 meetings. The action taken in overcoming the low learning outcomes of students is a Cooperative Learning approach type Group Investigation. Student learning outcomes data are collected by conducting tests at the end of each cycle. Furthermore, the collected data were analyzed using qualitative descriptive.       From the results of the data analysis, it was found that in the first cycle the learning outcomes of students still did not reach the established indicators, that of the 37 students who took the test, only 23 (62.16%) received a score of 80, while in the second cycle the learning outcomes of students had improved. from completeness individually or classical. Of the 37 people who completed individually, there were 36 people (97.30%). So it has exceeded the predetermined target of ≥ 85% of students get a score of demikian 80. Thus it can be concluded that the Cooperative Learning approach type Group Investigation can improve the learning outcomes of students in learning science grade VIII-A SMP Negeri 7 Mataram. For that the teachers and schools can use the Cooperative Learning approach type Group Investigation to improve student learning outcomes in learning